2018
DOI: 10.2337/db17-1513
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Epidermal Growth Factor Receptor Activation Is Associated With Improved Diabetic Nephropathy and Insulin Resistance in Type 2 Diabetes

Abstract: Previous studies by us and others have indicated that renal epidermal growth factor receptors (EGFR) are activated in models of diabetic nephropathy (DN) and that inhibition of EGFR activity protects against progressive DN in type 1 diabetes. In this study we examined whether inhibition of EGFR activation would affect the development of DN in a mouse model of accelerated type 2 diabetes (BKS with endothelial nitric oxide knockout [eNOS]). eNOS mice received vehicle or erlotinib, an inhibitor of EGFR tyrosine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 40 publications
7
67
2
Order By: Relevance
“…A previous study revealed that inhibition of EGFR tyrosine kinase activity amelio- Diabetes Metab J 2020 Forthcoming. Posted online 2020 https://e-dmj.org rated insulin resistance [41]. In the present study, differential expression analyses using four GEO datasets confirmed that EGFR may be a novel gene for the risk of T2DM.…”
Section: Discussionsupporting
confidence: 73%
“…A previous study revealed that inhibition of EGFR tyrosine kinase activity amelio- Diabetes Metab J 2020 Forthcoming. Posted online 2020 https://e-dmj.org rated insulin resistance [41]. In the present study, differential expression analyses using four GEO datasets confirmed that EGFR may be a novel gene for the risk of T2DM.…”
Section: Discussionsupporting
confidence: 73%
“…This may be explained that TKIs indirectly improves insulin sensitivity by inhibiting EGFR. Furthermore, one recent study has indicated that inhibition of EGFR by erlotinib is associated with improved diabetic nephropathy and insulin resistance in animal model with type 2 diabetes [87]. The above results are also associated with the low risk of renal disorder in the present meta-analysis.…”
Section: Plos Onesupporting
confidence: 56%
“…CDDP: cisplatin; GL: Ganoderma lucidum; EOD: every other day; EGFR: epidermal growth factor receptor. 9 Oxidative Medicine and Cellular Longevity potential for AKI during endotoxemia and diabetic nephropathy [74,75]. Our results showed that the upregulation of EGFR, following CDDP injection, was significantly downregulated in rats treated with GL, and this correction was associated with the improvement that occurred in nephrotoxicity indices.…”
mentioning
confidence: 61%